ANALISIS EFEK MEDIASI BUDAYA KERJA PADA PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI Studi pada Dinas Komunikasi dan Informatika, Statistik dan Persandian Kabupaten Gunung Mas - Olivia Winda Ony Panjaitan; Frisda Kristiana (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2019)
The purpose of this study was to examine the mediating effect of work culture on the influence of leadership on employee performance. The study was conducted at the Office of Communication and Information, Statistics and Baths of Gunung Mas Regency with the number of respondents in the study were 49 employees with saturated sampling techniques. The collected data was analyzed through the Structural Equation Modeling (SEM) approach with the Partial Least Square technique. Software tools used by SmartPLS 3.2.7. The results showed that work culture had a positive and significant effect on performance; leadership has a positive and significant effect on work culture; leadership has a positive and significant effect on work, and work culture mediates the influence of leadership on employee performance.